Lack of Correlation between Anterior Cruciate Ligament Injury Risk Factors and Its Severity Degree - Darmawan, Muhammad Arief; Heristyorini, Ayodya; Ramadhani, Isniani; Agustini, Diana (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2024)
Anterior Cruciate Ligament (ACL) injury is a prevalent, severe, and costly orthopedic condition affecting individuals. The ACL prevalence is related to harder activity. This study aims to explore the correlation between age, Body Mass Index (BMI), and occupational history with the severity of ACL injuries at Gatot Soebroto Central Army Hospital. The analysis adopted a cross-sectional design and utilized the chi-square test, examining 121 medical records from 2 groups of patients that were civilians and National Armed Forces/TNI. There are 88.4% of 19 – 44 years; 50.4% with normal BMI, and 49.6% overweight/obese; 49.6% civilian and 50.4% TNI; 70.2% with total tear, and the rest was partial tear of participants. The data analysis indicated p-values of 0.633 for age, 0.953 for BMI, and 0.126 for occupational history concerning their association with the severity of ACL injuries. Additionally, all three variables showed Odds Ratio (OR) values greater than 1, with the OR for age being 1.608, for BMI being 1.024, and for employment history being 1.853. All of these findings suggested that there was no significant correlation between these variables and the severity of ACL injuries. Despite the lack of significant correlation, these risk factors may still increased susceptibility to severe ACL injuries.